1995
DOI: 10.1063/1.469654
|View full text |Cite
|
Sign up to set email alerts
|

Abinitio molecular dynamics simulation of the solvation and transport of hydronium and hydroxyl ions in water

Abstract: Charge defects in water created by excess or missing protons appear in the form of solvated hydronium H3O+ and hydroxyl OH− ions. Using the method of ab initio molecular dynamics, we have investigated the structure and proton transfer dynamics of the solvation complexes, which embed the ions in the network of hydrogen bonds in the liquid. In our ab initio molecular dynamics approach, the interatomic forces are calculated each time step from the instantaneous electronic structure using density functional method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
607
2
6

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 813 publications
(662 citation statements)
references
References 53 publications
47
607
2
6
Order By: Relevance
“…329 Specifically, it is shown that the oxygen-oxygen distances in the OH hydrogen bonded complex are shorter than for the other water molecules. This situation is similar to that observed in bulk solution, 330,331 and implies that the rate-limiting step for the process of the OH migration, either in solution or on a surface, is the rearrangement of the local oxygen environment and not the proton transfer event. [329][330][331] In this way, the first two steps may be viewed analogously as an electron transfer facilitated migration of OH À from solution onto the surface, with a fast initial discharge step and a slow hydrogen bonding restructuring process.…”
Section: Mechanistic Studies Of the Oersupporting
confidence: 79%
“…329 Specifically, it is shown that the oxygen-oxygen distances in the OH hydrogen bonded complex are shorter than for the other water molecules. This situation is similar to that observed in bulk solution, 330,331 and implies that the rate-limiting step for the process of the OH migration, either in solution or on a surface, is the rearrangement of the local oxygen environment and not the proton transfer event. [329][330][331] In this way, the first two steps may be viewed analogously as an electron transfer facilitated migration of OH À from solution onto the surface, with a fast initial discharge step and a slow hydrogen bonding restructuring process.…”
Section: Mechanistic Studies Of the Oersupporting
confidence: 79%
“…Not only may an excess proton in a water medium move via simple vehicular diffusion but can also travel via 'structure diffusion' or the Grotthuss shuttling mechanism. As complicated as the mobility of an excess proton may be in bulk water 40,121,122 the process is even more involved in a hydrated PFSA membrane due to the confinement of the water in an environment with a high density of both sulfonate groups tethered to the polymer and other hydrated protons. In an effort to provide a framework for understanding the conduction of protons in PFSA and other ionomers, the authors have suggested that the important ingredients include processes described as: complexity, connectivity, and cooperativity.…”
Section: This Journal Is C the Owner Societies 2007mentioning
confidence: 99%
“…The Mg-O separation in Mg 2+ hexahydrate results (2.115 Å) is somewhat larger than the MP2 result 2.081 Å. 39 The Car-Parrinello method has been used extensively to study the properties of water, [40][41][42][43][44][45] ion and molecule solvation, [46][47][48][49] and simple chemical reactions in water, 50,51 where fictitious electron masses between 600 and 1100 m e allow time steps of 0.1-0.2 fs. The hydrogen atoms are often replaced by deuterium in order to allow larger time steps.…”
Section: Methods Of Calculationmentioning
confidence: 99%